Taxonomic notes of the genus Ripiphorus Bosc d’Antic (Coleoptera: Ripiphoridae: Ripiphorinae) from China, with description of a new species - Jiang, Lan-Xing; Wang, Shao-Peng; Pan, Zhao (Zootaxa, 2024)
The Chinese species of the ripiphoride genus Ripiphorus Bosc d’Antic, 1791 are taxonomically reviewed. A new species, R. curvispinus Pan, sp. nov., is discovered from Beijing and distinguished from its congeners by the distinctly curved metatibial inner spur. The difference between R. curvispinus Pan sp. nov. and R. chalcidoides (Gressitt, 1941) is confirmed using phylogenetic analysis and molecular species definition based on mtDNA COI sequences. Furthermore, Ripiphorus subdipterus Fabricius, 1792 is newly recorded for China. All Ripiphorus species occurring in China are described, illustrated and keyed.